2018
DOI: 10.1007/s12264-018-0277-8
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Excites Rat GABAergic Ventral Pallidum Neurons via Co-activation of H1 and H2 Receptors

Abstract: The ventral pallidum (VP) is a crucial component of the limbic loop of the basal ganglia and participates in the regulation of reward, motivation, and emotion. Although the VP receives afferent inputs from the central histaminergic system, little is known about the effect of histamine on the VP and the underlying receptor mechanism. Here, we showed that histamine, a hypothalamic-derived neuromodulator, directly depolarized and excited the GABAergic VP neurons which comprise a major cell type in the VP and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The increase in action potential frequency promoted by histamine in deep-layer cortical neurons is in accordance with the increased excitability previously reported for neurons in other regions of the CNS, namely thalamus (McCormick and Williamson, 1991), layer 6b of the primary somatosensory cortex (Wenger Combremont et al, 2016), entorhinal cortex (Cilz and Lei, 2017), ventral pallidum (Ji et al, 2018), striatum (Zhuang et al, 2018), and spinal cord (Wu et al, 2019). Furthermore, the lack of difference in H 1 R density supports that the electrophysiological changes observed in the offspring of diabetic rats rely mainly on morphological alterations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The increase in action potential frequency promoted by histamine in deep-layer cortical neurons is in accordance with the increased excitability previously reported for neurons in other regions of the CNS, namely thalamus (McCormick and Williamson, 1991), layer 6b of the primary somatosensory cortex (Wenger Combremont et al, 2016), entorhinal cortex (Cilz and Lei, 2017), ventral pallidum (Ji et al, 2018), striatum (Zhuang et al, 2018), and spinal cord (Wu et al, 2019). Furthermore, the lack of difference in H 1 R density supports that the electrophysiological changes observed in the offspring of diabetic rats rely mainly on morphological alterations.…”
Section: Discussionsupporting
confidence: 88%
“…Histamine increases neuronal excitability in several regions of the CNS such as the thalamus ( McCormick and Williamson, 1991 ), layer 6b of the primary somatosensory cortex ( Wenger Combremont et al, 2016 ), entorhinal cortex ( Cilz and Lei, 2017 ), ventral pallidum ( Ji et al, 2018 ), striatum ( Zhuang et al, 2018 ), and spinal cord ( Wu et al, 2019 ). Therefore, we recorded deep layer neurons from P21 pups by injecting depolarizing current in increasing steps under basal and stimulated (1–100 μM histamine) conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HA increases neuronal excitability through H 1 R activation ( McCormick and Williamson, 1991 ; Ji et al, 2018 ; Zhuang et al, 2018 ). Therefore, H 1 R density was determined in P21 frontal cortex membranes from both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed that activation of both postsynaptic H1R and H2R co-mediates histamine induced-neuron excitability in several kinds of neurons. For instance, histamine excites dopamine D1 and D2 receptor-expressing striatal GABAergic medium spiny projection neurons, nucleus basalis cholinergic neurons, substantia nigra pars reticulate inhibitory projection neurons, GABAergic ventral pallidum neurons, superior vestibular nuclear neurons, and inferior vestibular nucleus neurons via postsynaptic H1R and H2R (Ji et al, 2018;Khateb, Fort, Pegna, Jones & Mühlethaler, 1995;Peng, Zhuang, He, Zhu & Wang, 2013;Zhou, Xu, Zhao, LeDoux & Zhou, 2006;Zhuang, Wu, Wu, Zhu & Wang, 2013;Zhuang et al, 2018). In medial vestibular nuclear neurons, histamine induces strong postsynaptic excitatory action by Na+-Ca²+ exchangers coupled to H1R and HCN linked to H2R (Zhang, Yu, Zhuang, Peng, Zhu & Wang, 2013).…”
Section: H2r and Neural Excitabilitymentioning
confidence: 99%